BRANDING PENDIDIKAN TINGGI JARAK JAUH TERHADAP LOYALITAS, HARGA DAN POPULARITAS - Jasrial Jasrial; Enceng Enceng; Deni Surapto (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2018)
Higher education competition refers to Permendikbud no.24 of 2012 concerning the implementation of distance education at universities (PT) which has opened opportunities and opportunities for other universities besides the Open University (UT) to organize distance education. Various strategies that can be applied to maintain the survival of an organization in the face of its competitors include, one of them is to pay attention to brand association and brand loyalty to the organization. One of the most important attributes is the brand. Brand equity relates to the level of brand recognition, brand quality believed, strong mental and emotional associations and other assets (Kotler, 2007). For the past 34 years, the Open University as the only college that provides distance education is the market leader and top of mind of distance education. Therefore the importance of building a brand and doing UT. The purpose of this study is: 1) to know the significance of each element of branding variables in building UT, 2) To know UT promotion in improving customer loyalty. The results showed by Structural Equation Modeling (SEM) analysis. Brand UT has a significant effect on the value of t-statistics of the influence of Brand UT on the Price of 6.866673, this value is greater than the t-table value of 1.98 for the 0.05 significance level (5%). Brand UT has a significant effect on Loyalty with the value of t-statistics of Brand UT's influence on Loyalty of 11.518046, this value is greater than the t-table value of 1.98 for the significant level of 0.05 (5%) and the value of the influence of Brand UT on Popularity 7.930576, this value is greater than the value of t-table 1.98 for the significant level 0.05 (5%).